2022
DOI: 10.3389/fphys.2022.892154
|View full text |Cite
|
Sign up to set email alerts
|

Nature vs. Nurture: Disentangling the Influence of Inheritance, Incubation Temperature, and Post-Natal Care on Offspring Heart Rate and Metabolism in Zebra Finches

Abstract: A historic debate in biology is the question of nature vs. nurture. Although it is now known that most traits are a product of both heredity (“nature”) and the environment (“nurture”), these two driving forces of trait development are rarely examined together. In birds, one important aspect of the early developmental environment is egg incubation temperature. Small changes (<1°C) in incubation temperature can have large effects on a wide-array of offspring traits. One important trait is metabolism, beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 94 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…This is most evident in ectotherms, owing to the pervasive effect of ambient temperature on their physiological processes ( Jonsson and Jonsson, 2019 ; Jonsson et al, 2022 ). However, it is also important for birds, where the temperature at which the eggs are incubated is now known to influence post-hatching traits such as metabolic rate ( Hope et al, 2022 ). This may explain why the basal metabolic rate of wintering wild great tits ( Parus major ) is negatively correlated with the ambient minimum temperature they experienced during incubation: it has been suggested that this is adaptive, with the metabolism of embryos experiencing a cold spring being programmed to cope with colder winters ( Broggi et al, 2022 ).…”
Section: The Triggers Of Developmental Plasticitymentioning
confidence: 99%
See 2 more Smart Citations
“…This is most evident in ectotherms, owing to the pervasive effect of ambient temperature on their physiological processes ( Jonsson and Jonsson, 2019 ; Jonsson et al, 2022 ). However, it is also important for birds, where the temperature at which the eggs are incubated is now known to influence post-hatching traits such as metabolic rate ( Hope et al, 2022 ). This may explain why the basal metabolic rate of wintering wild great tits ( Parus major ) is negatively correlated with the ambient minimum temperature they experienced during incubation: it has been suggested that this is adaptive, with the metabolism of embryos experiencing a cold spring being programmed to cope with colder winters ( Broggi et al, 2022 ).…”
Section: The Triggers Of Developmental Plasticitymentioning
confidence: 99%
“…Given the difficulty in separating these intergenerational effects and their complex terminology, in this paper I consider transgenerational and early developmental effects together, for the simple reason that in many species it can be hard to determine whether it is the parent or the developing offspring that is responding to an environmental cue. A further reason why transgenerational effects can be hard to unravel in nature is that they can derive from either parent ( Hope et al, 2022 ; Papatheodoulou et al, 2022 ), and their impact on offspring can be sex-dependent: for example, the effects of parental stress can depend on the sex of both the parent and the offspring ( Hellmann et al, 2020a ). These sex×stress×generation interactions become ever more complex by the grandoffspring F2 generation ( Hellmann et al, 2020b ).…”
Section: Introduction: Compensatory Responses As a Form Of Hidden Pla...mentioning
confidence: 99%
See 1 more Smart Citation